Mapping The Science, Technology, Engineering and Mathematics (STEM) Research Network in Science and Environmental Education: A Bibliometric Review - Luki Yunita; Salamah Agung; Nur Kholiq Majid; Rifqa Masliah Humairah (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Research on Science, Technology, Engineering, and Mathematics (STEM) in science education and environmental education continues to grow as an effort to improve the quality of learning and support sustainable development. However, studies mapping research developments in these fields are still limited. This study aims to analyze STEM research trends in science education and environmental education using a bibliometric approach. Data were obtained through Publish or Perish (PoP) using the Google Scholar database using the keywords STEM Chemistry Education and Environmental Education. A total of 193 articles published between 2022 and 2026 were collected and then selected, resulting in 22 articles for analysis using VOSviewer through network visualization, overlay, density, and co-authorship. The results show that the keywords education, science, science education, learning, STEM, and environmental education are the most dominant themes. In addition, the topics of environmental awareness, artificial intelligence, application, and science teaching have potential as future research directions, while co-authorship analysis indicates that collaboration between authors is still relatively limited. This study provides an overview of the development of STEM research and opportunities for its future development.